“Determinación de las concentraciones de material particulado orgánico volátil en el barrio la esperanza, ciudad de Riobamba, por incidencia de aserraderos” - Lara Basantes, Cristian Artuto (2018)
The excessive presence of sawmills in urban areas that do not have neither an infrastructure nor the adequate work equipment. They generate organic dust less than 10 μm (PM10) to the surrounding environment. This type of particulate material is related to some damages to respiratory system. The present investigation was done in the neighborhood of "La Esperanza" in the city of Riobamba, with the purpose of evaluating the degree of contamination by PMV and PMS. Those have caused health problems in its residents, such as throat and irritated sight. An analysis on PMV was made with the use of the DustTrak™ II equipment. The PMS was collected in Petri boxes by the passive method. The measurements were made in the October-November 2017 period, registering maximum values of 42.67 μg/m³, 35.5 μg/m³, 29.83 μg/m³, and minimum values of 7.33 μg/m³, 8.67 μg/m³ and 4.67 μg/m³ for PM10, PM4 and PM2,5, respectively; for PMS, 6 samples were analyzed, of which the highest concentration is found in the main rondure of the sector with 1.36 mg/cm²/month. They exceeds the LMP established by Ecuadorian legislation and the OMS. The morphology of the sediment particles in the MO were analyzed, which have irregular shapes, identifying long, short, flat, compact and torn fibers. Finally, a wind direction and wind speed map were generated with the data of the INAMHI meteorological stations, showing the spatial variation of the PMV behavior of 2.5 μm, with an average velocity of 1.3 m/s and a NO direction.